In the Presence of the Past, in the Shadow of the 'Other': Women Journalists in Post-war Germany - Barton, Deborah (Gendering post-1945 German history: entanglements, 2019)
"Although 'entanglement' has become a keyword in recent German history scholarship, entangled studies of the postwar era have largely limited their scope to politics and economics across the two Germanys while giving short shrift to social and cultural phenomena like gender. At the same time, historians of gender in Germany have tended to treat East and West Germany in isolation, with little attention paid to intersections and interrelationships between the two countries. This groundbreaking collection synthesizes the perspectives of entangled history and gender studies, bringing together established as well as upcoming scholars to investigate the ways in which East and West German gender relations were culturally, socially, and politically intertwined"--
Keywords: 1945-1990; 20th century; Germany; History; Sex role